2017
DOI: 10.3390/app7080769
|View full text |Cite
|
Sign up to set email alerts
|

The Synchrosqueezing Algorithm Based on Generalized S-transform for High-Precision Time-Frequency Analysis

Abstract: Abstract:In this paper, a new time-frequency analysis method-Synchrosqueezing Generalized S-transform (SSGST)-is proposed to meet the needs of high-resolution seismic signal processing and interpretation. The basic wavelet of the generalized S-transform (GST) in the paper is a modulated harmonic wave with four undetermined parameters that can be constructed by adjusting the four parameters to make the GST more suitable for seismic signals processing. The SSGST method squeezes and reconstructs the complex coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…In 2017, synchrosqueezing generalized S-transform (SSGST) is proposed by Chen H. et al [ 34 ]. This method based on the generalized S-transform (GST) with four parameters which is proposed by Gao J.H.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, synchrosqueezing generalized S-transform (SSGST) is proposed by Chen H. et al [ 34 ]. This method based on the generalized S-transform (GST) with four parameters which is proposed by Gao J.H.…”
Section: Methodsmentioning
confidence: 99%
“…Inspired by the squeezes along the frequency direction [ 31 , 32 , 33 ], Chen H. et al proposes a new high resolution time-frequency analysis method which is named synchrosqueezing generalized S-transform (SSGST) in 2017 [ 34 ]. This method introduces GST to replace the WT of synchrosqueezing wavelet (SST) [ 35 , 36 ], squeezes, and reconstructs the complex coefficient spectra of GST results along the frequency direction, so that the energy distributions on the time-frequency spectra are concentrated around the real instantaneous frequency of the target signal and shows a high time-frequency resolution.…”
Section: Introductionmentioning
confidence: 99%
“…en the transform bypasses the window size problem of STFT while holding some WT properties. e permanent trend of the standard transform wavelet function restricts its applications, so several authors have suggested different forms for the S-transform [8]. On the other hand, S-transform may be viewed as a type of windowed Fourier transform, where the length of the centered window at τ is inversely proportional to f. Discrete ST transforms convert Advances in Civil Engineering an n point signal into an n 2 point one, so they are highly redundant.…”
Section: S-transformmentioning
confidence: 99%
“…The synchrosqueezing generalized S transform (SSGST) [4] is derived from the generalized S transform [5] . It combines the advantages of the synchronous extrusion algorithm and the traditional GST algorithm.…”
Section: Principle 21 Ssgstmentioning
confidence: 99%